2023
DOI: 10.3390/ani13243884
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Alliaceae Encapsulated Extract on Growth Performance, Gut Health, and Intestinal Microbiota in Broiler Chickens Challenged with Eimeria spp.

Gonzalo Villar-Patiño,
María del Carmen Camacho-Rea,
Myrna Elena Olvera-García
et al.

Abstract: This study analyzed the effects of an Alliaceae encapsulated extract (AE-e) on daily gain (ADG), feed intake (ADFI), feed conversion ratio (FCR), oocysts per gram of feces (OPG), intestinal lesion (LS), and microbiota composition in broilers challenged with Eimeria spp. A total of 4800 one day Cobb-500 were allotted into 10 treatment groups with 12 replicates of 40 birds in a 2 × 4 + 2 factorial arrangement. The first factor was non-challenged (NC) or challenged (C), the second was four levels of AE-e added in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Although E. acervulina does not target the cecum and ileum directly, a study has shown an E. acervulina infection can affect cecal microbiota diversity 12 , and it has been suggested that E. acervulina infection could affect cecal microbiota by increasing endogenous loss of proteins and undigested dietary proteins in the GIT 13,14 . While there are various studies investigating mixed Eimeria species infections on the cecum and/or ileum 13,[15][16][17] , less is known on the individual effects of E. acervulina. The aim of this study was to determine the effect of E. acervulina on the luminal and mucosal microbiota of both the cecum and ileum at multiple time points during infection.…”
mentioning
confidence: 99%
“…Although E. acervulina does not target the cecum and ileum directly, a study has shown an E. acervulina infection can affect cecal microbiota diversity 12 , and it has been suggested that E. acervulina infection could affect cecal microbiota by increasing endogenous loss of proteins and undigested dietary proteins in the GIT 13,14 . While there are various studies investigating mixed Eimeria species infections on the cecum and/or ileum 13,[15][16][17] , less is known on the individual effects of E. acervulina. The aim of this study was to determine the effect of E. acervulina on the luminal and mucosal microbiota of both the cecum and ileum at multiple time points during infection.…”
mentioning
confidence: 99%